Microbial oils as food additives: recent approaches for improving microbial oil production and its polyunsaturated fatty acid content. (February 2016) - Bellou, Stamatia; Triantaphyllidou, Irene-Eva; Aggeli, Dimitra; Elazzazy, Ahmed Mohammed; Baeshen, Mohammed Nabih; Aggelis, George
Graphical abstract: Highlights: Oleaginous fungi and microalgae are suitable sources of PUFAs. Genetic engineering for improving oil accumulation and fatty acid composition. Overexpression of key-enzymes involved in lipid biosynthesis. Repression of β-oxidation pathway. Enhancement of PUFA biosynthesis via genetic manipulation. Abstract : In this short review, we summarize the latest research in the production of polyunsaturated microbial oils that are of interest in food technology. The current research targets the productivity of oleaginous microorganisms, as well as the biosynthesis of particular polyunsaturated fatty acids (PUFAs). The most important efforts target the efficiency of the oleaginous machinery, via overexpression of key-enzymes involved in lipid biosynthesis, as well as the minimization of lipid degradation, by repressing genes involved in the β-oxidation pathway. The production of specific PUFAs is approached by homologous or heterologous expression of specific desaturases and elongases involved in PUFA biosynthesis in oleaginous microorganisms. New perspectives, such as the production of triacylglycerols of specific structure and the employment of adaptive experimental evolution for creating robust oleaginous strains able to produce PUFAs are also discussed.